Four eyes - Ogle, Rex (Ogle, Rex. Four eyes (Series), 2023)
Sixth grade isn't going well for Rex. He's the only kid who hasn't gotten a growth spurt, his closest friend starts hanging out with the "cool kids," and he's become a prime target for bullies. Then, things go from bad to worse when he finds out he needs glasses and his family can only afford the ugliest pair in the store, and Rex is desperate to find a way to fit in when everything he does seems to make him stand out.